Poor Health Literacy and Medication Burden Are Significant Predictors for Inadequate Bowel Preparation in an Urban Tertiary Care Setting. Issue 9 (October 2019) - Kunnackal John, George; Thuluvath, Avesh J.; Carrier, Hairong; Ahuja, Nitin K.; Gupta, Ekta; Stein, Ellen
Abstract : Goals: The goal of this study was to identify factors impacting the quality of bowel preparation in an urban tertiary care setting. Background: Inadequate bowel preparation is encountered in 17% to 32% of colonoscopies performed in the United States. Suboptimal colonic visualization reduces the yield of screening colonoscopies and increases healthcare costs because of longer procedure times and aborted procedures. Study: We performed a cross-sectional survey in patients undergoing outpatient colonoscopy within the Johns Hopkins Health System. A Boston Bowel Preparation Score (BBPS) score of <5 was considered inadequate. Fisher's exact, χ 2 tests and univariate and multivariate binary logistic regression were performed to assess the strength of the association for selected factors with a BBPS<5. Results: In total, 467 patients (76.3% response rate) completed the survey between August 2017 and October 2017. The median BBPS score was 7, and 81.4% of patients had an adequate bowel preparation (BBPS≥5). There was significant association between bowel preparation adequacy and level of education, health literacy, functional status, income, and medication burden. When adjusted for other factors, poor confidence in filling forms (OR, 24.1; P <0.001), multiple daily prescription medications (OR, 12.49; P =0.02) and poor functional status (OR, 2.82; P =0.03) had the highest odds of predicting inadequate bowel preparation. Conclusions: Inadequate bowel preparation is a significant problem accounting for reduced yield of screening and increased health care costs. Poor health literacy, functional status, and number of daily medications are significant factors predicting inadequate bowel preparation in the tertiary care setting.